Inflammation drives wound hyperpigmentation in zebrafish by recruiting pigment cells to sites of tissue damage - Mathieu Lévesque; Yi Feng; Rebecca A. Jones; Paul Martin (The Company of Biologists, 2013)
SUMMARY In humans, skin is the largest organ and serves as a barrier between our body and the outside world. Skin protects our internal organs from external pathogens and other contaminants, and melanocytes within the skin protect the body from damage by ultraviolet light. These same pigment cells also determine our skin colour and complexion. Skin wounding triggers a repair response that includes a robust recruitment of inflammatory cells, which function to kill invading microbes and clear away cell and matrix debris. Once at the wound site, these innate immune cells release a barrage of cytokines that direct the activities of other cells during the repair process. Tissue damage and repair also frequently lead to alterations in skin pigmentation, in particular to wound hyperpigmentation. In this study, we describe a model of wound hyperpigmentation in the translucent zebrafish larva, where we can live-image the recruitment of melanocytes and their precursors, melanoblasts, to the wound site. We show that these pigment cells are drawn in after the initial recruitment of innate immune cells and that the inflammatory response is essential for wound hyperpigmentation. This new model will allow us to uncover the molecular link between immune and pigment cells during tissue repair and to screen for potential therapeutics to dampen wound hyperpigmentation.